The Effectiveness of Puppets as an Educational Tool to Enhance Dental Health Knowledge Among Elementary School Students in Surabaya, Indonesia - Meisy Yuliana Putri; Ratih Larasati; Silvia Prasetyowati; Anshad Ansari (International Journal of Advanced Health Science and Technology, 2024)
Children may have a high debris index because they do not know enough about maintaining oral hygiene. The high debris index in grade II students of SDN Bendul Merisi Surabaya is a problem in this study. The purpose of this study was to evaluate how well the response of grade II students of SDN Bendul Merisi Surabaya to counseling using tooth dolls to improve their understanding of maintaining good oral health. Quantitative research was used in this methodology. 52 students registered in grade II of SDN Bendul Merisi Surabaya were the focus of this study. The tool used to collect data was a questionnaire. The survey sheet was the tool used to collect data. The data analysis technique used was the Wilcoxon test. The results of students' knowledge before counseling using tooth dolls were in the poor criteria, after counseling using tooth dolls it was in the good category, in addition, P < 0.05 which was indicated by the Wilcoxon test effectiveness test showed that tooth dolls had an impact on improving students' understanding in maintaining oral health. The study concluded that the counseling of tooth puppet media is a very good way to improve the understanding of grade II students about maintaining oral health at SDN Bendul Merisi Surabaya. INDEX TERMS Knowledge, Tooth Doll Media, Dental and Oral Health Maintenance.